2015
DOI: 10.1249/mss.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Long-Term Endurance Training on V·O2 Kinetics

Abstract: The kinetics of the adjustment of pulmonary oxygen uptake (VO 2 )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 82 publications
7
34
0
Order By: Relevance
“…Additionally, sex hormone-binding globulin (SHBG) is positively correlated with age, thereby attenuating the unbound fraction of testosterone, which is available for androgen receptor interactions (4, 5). With the age-associated reduction in anabolic hormone production, reductions in cardiorespiratory fitness (6), muscle strength (7) and muscle power (8) are also observed. Furthermore, significant correlations between testosterone and measures of physical performance in older adults have been observed (9).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, sex hormone-binding globulin (SHBG) is positively correlated with age, thereby attenuating the unbound fraction of testosterone, which is available for androgen receptor interactions (4, 5). With the age-associated reduction in anabolic hormone production, reductions in cardiorespiratory fitness (6), muscle strength (7) and muscle power (8) are also observed. Furthermore, significant correlations between testosterone and measures of physical performance in older adults have been observed (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our laboratory has proposed that improvements in O 2 delivery and/or distribution to the active tissues play a critical role in the speeding of normalV ˙ O 2 kinetics observed after an exercise training intervention (Murias et al., 2010b,c) or in chronically trained individuals (Grey et al., ). Others, however, have proposed that in young healthy individuals, improvements in O 2 extraction (Bailey et al., ) and/or enhanced intracellular metabolic control (i.e., faster activation of pyruvate dehydrogenase and other oxidative enzymes; McKay et al., ) are mainly responsible for the faster normalV ˙ O 2 kinetics observed shortly after the commencement of an exercise training program.…”
mentioning
confidence: 99%
“…Importantly, recent studies have shown that different interventions can decrease TV O 2 in older individuals to values similar to those observed in their young counterparts (23,39,57,58), opening the debate as to whether aging per se, or other factors that normally accompany, but are not requisite with, aging (such as poorer cardiovascular function and decreased mitochondrial enzymes activity likely related to reduced fitness levels), is responsible for the slower rate of adjustment in the V O 2 response in the elderly.…”
mentioning
confidence: 73%
“…Indeed, in three other studies in which V O 2 kinetics responses were compared in older and young individuals, the rate of adjustment of oxidative phosphorylation was similar between groups (12,13,38). In addition, a recent paper has demonstrated that older, chronically trained men have V O 2 kinetics that is similar to those of young individuals (39). This is an important characteristic of this response, as it shows not only that some older participants might display a ''fast'' V O 2 kinetics but also that young, healthy individuals might exhibit a ''slow'' response as previously demonstrated (62,63).…”
Section: O 2 Kinetics In Older Adultsmentioning
confidence: 90%